Higher Self Efficacy Associated with Lower Academic Procrastination: Efikasi Diri yang Lebih Tinggi Berkaitan dengan Penundaan Akademik yang Lebih Rendah - Pandu Bagus; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Academic procrastination is commonly experienced by university students and involves delaying academic responsibilities that may disrupt learning processes. Specific Background: Self efficacy reflects an individual’s belief in their ability to organize and complete academic tasks and is related to behavioral regulation. Knowledge Gap: Research examining the relationship between self efficacy and academic procrastination within specific university student populations remains limited. Aims: This study aimed to analyze the relationship between self efficacy and academic procrastination among university students. Results: A quantitative correlational design was applied using self efficacy and academic procrastination questionnaires analyzed with Pearson product moment correlation. The results showed a significant negative relationship, indicating that students with higher self efficacy demonstrated lower procrastination levels. Novelty: This study provides empirical evidence within the examined university student population regarding psychological determinants of academic procrastination. Implications: The findings support the inclusion of self efficacy development in academic counseling and student support programs to address delayed academic task completion. Highlights: Statistical Testing Identified an Inverse Correlation Between Confidence in Task Ability and Delay Behavior. Questionnaire Analysis Demonstrated Variability in Postponement Patterns Among Participants. Psychological Capability Belief Was Identified as a Factor Related to Delayed Academic Responsibility. Keywords: Self Efficacy, Academic Procrastination, University Students, Academic Behavior, Student Task Completion